2017
DOI: 10.1097/md.0000000000009046
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography imaging features of hepatic perivascular epithelioid cell tumor

Abstract: Rationale:Perivascular epithelioid cell tumor (PEComa) is a rare tumor which is most frequently found in uterus. The tumor arising from liver is extremely uncommon.Patient concerns:A 36-year-old female with abdominal distention, cramps, and low-grade fever for over 15 days. The patient had a history of gastric adenocarcinoma with ovarian, celiac lymph nodes, and retroperitoneal lymph nodes metastases.Diagnoses:Computed tomography (CT) imaging demonstrated an ill-defined heterogeneous hypo-dense mass in segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 23 publications
2
14
1
Order By: Relevance
“…Thus, the expression of Melan-A, HMB45, and SMA are the most important evidence for hepatic PEComa. This result was consistent with other studies [1–31] . Surprisingly, these markers were not 100% positive in previously reported cases, and Folpe et al [30] found that only 80% of PEComas were simultaneously positive for melanocyte and smooth muscle cell markers.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, the expression of Melan-A, HMB45, and SMA are the most important evidence for hepatic PEComa. This result was consistent with other studies [1–31] . Surprisingly, these markers were not 100% positive in previously reported cases, and Folpe et al [30] found that only 80% of PEComas were simultaneously positive for melanocyte and smooth muscle cell markers.…”
Section: Discussionsupporting
confidence: 91%
“…According to the results of this study, hepatic PEComas were more likely to occur in the right lobe. However, combined with the findings from other studies, as the sample size increases, the number of tumours occurring in the left lobes was approximately equal to the right [1–19] …”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations